The Clinical Value of Echocardiography and Acoustic Cardiography to Monitor Patients Undergoing Anthracycline Chemotherapy. Issue 4 (14th November 2012) - Toggweiler, Stefan; Odermatt, Yvonne; Brauchlin, Andreas; Zander, Thilo; Müller, Andrea; Zuber, Michel; Winterhalder, Ralph; Erne, Paul
Abstract Background Investigate the usefulness of echocardiography and acoustic cardiography to monitor patients exposed to anthracycline chemotherapy. Hypothesis Serial echocardiographies to monitor systolic function may not be neccessary in all patients undergoing anthracycline chemotherapy. Methods In a prospective study, consecutive patients undergoing anthracycline‐containing chemotherapy were evaluated with echocardiography and acoustic cardiography at baseline, after completion of chemotherapy, and after a median follow‐up of 3.8 years. Systolic dysfunction was defined as a left ventricular ejection fraction ≤50%. Results A total of 187 patients (83% female) with a mean age of 55 ± 14 years underwent chemotherapy for breast cancer (73%), malignant lymphoma (23%), and sarcoma (4%). None of the patients had systolic dysfunction at baseline. Patients were treated with doxorubicin 276 ± 74 mg/m2 or epirubicin 317 ± 55 mg/m2. After chemotherapy, 170 (91%) had normal systolic function, 8 (4%) developed systolic dysfunction, and 9 (5%) had died. Of those 8 patients with systolic dysfunction, 4 (50%) improved to normal systolic function, 1 (13%) remained unchanged, and 3 (37%) died. Patients with normal systolic function after chemotherapy had a mortality rate of 3.5%, and 1.8% developed late systolic dysfunction. Acoustic cardiography‐derived percent electromechanical activation time >12.4% had a sensitivity of 88% and a specificity of 84% to identify patients with systolic dysfunction (area under the receiver operating characteristic curve 0.87). Conclusions Patients with systolic dysfunction early after anthracycline treatment had worse outcome. Acoustic cardiography was able to identify these patients with a high sensitivity and specificity. Based on the findings of this study, we propose a simple algorithm to monitor patients undergoing anthracycline‐containing chemotherapy. The authors have no funding, financial relationships, or conflicts of interest to disclose.